2011
DOI: 10.1007/s11357-011-9248-y
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and character of resistance-training-induced increase in tendon stiffness at old age is gender specific

Abstract: Human tendon mechanical properties are modified with loading. Moreover, there are indications that the training response in the tendon is gender specific. The aim of the current study was to examine whether in vivo patella tendon stiffness (K) differentially alters with training in older males compared with females. We also aimed to identify which endocrine pathway underlies the responses. Maximal knee extensor forces were also monitored to determine the training effect on muscle function. Fourteen healthy, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 53 publications
4
26
4
Order By: Relevance
“…In an elderly population, 14 weeks of high load resistance training (at 80 % 5RM) has been shown to increase the stiffness of the patella tendon by 65 % (Reeves et al 2003a). Similar findings have been reported by others including descriptions on how training modality and/or gender impact on the tendon responses (Onambele et al 2008;Onambele-Pearson and Pearson 2012). In contrast, it has been observed that lower intensity exercise in the form of a 6-month progressive walking programme does not influence tendon properties in older adults (Kubo et al 2008).…”
Section: Introductionsupporting
confidence: 88%
“…In an elderly population, 14 weeks of high load resistance training (at 80 % 5RM) has been shown to increase the stiffness of the patella tendon by 65 % (Reeves et al 2003a). Similar findings have been reported by others including descriptions on how training modality and/or gender impact on the tendon responses (Onambele et al 2008;Onambele-Pearson and Pearson 2012). In contrast, it has been observed that lower intensity exercise in the form of a 6-month progressive walking programme does not influence tendon properties in older adults (Kubo et al 2008).…”
Section: Introductionsupporting
confidence: 88%
“…5) to stimulate further adaptive changes in the Achilles tendon in older female adults. It should be stated, that post-menopausal elderly women have a diminished tendon modulation to exercise (Onambele- Pearson and Pearson, 2012). However, whether or not the identified stagnation in the muscle and tendon adaptation can be related to a possible sex-specific reduction in the ability to respond to the anabolic stimuli in the musculotendinous tissue (Hansen and Kjaer, 2014) cannot be answered based on the current study design.…”
Section: Control Groupmentioning
confidence: 87%
“…strength training) have confirmed that tendons preserve their adaptability to mechanical loading even in older age (Grosset et al, 2014;Karamanidis et al, 2014;Maganaris et al, 2004;OnambelePearson and Pearson, 2012;Reeves et al, 2003a,b). One common finding of the limited number of exercise training intervention studies in older participants is a post-intervention increase in tendon stiffness and Young's modulus, in the absence of any changes in tendon dimensions (Grosset et al, 2014;Onambele-Pearson and Pearson, 2012;Reeves et al, 2003a). The lack of changes in tendon CSA may have been caused by the limited number of transversal scans (typically from 3 regions) taken along the tendon, which may exclude regional CSA changes as reported in studies with younger adults in response to strength training (Arampatzis et al, 2007a;Kongsgaard et al, 2007;Magnusson and Kjaer, 2003;Seynnes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similar magnitudes of change in stiffness have been demonstrated for human lower limb tendons in response to resistance training and bed rest. Twelve to 14 weeks of resistance training has been shown to facilitate a 50-84% increase in tendon stiffness and elastic modulus in young Malliaras et al, 2013) and older (Reeves et al, 2003;Onambele-Pearson and Pearson, 2012) adults. Conversely, 21 and 90 days of bed rest may reduce tendon stiffness (and elastic modulus) by 29% (De Boer et al, 2007) and 58% (Reeves et al, 2005), respectively.…”
Section: Discussionmentioning
confidence: 99%